Environmental management within the indigenous perspective - Andrian Dolfrianda Huruta; Maria Dyah Kurniasari (Faculty of Social and Political Science, Universitas Airlangga, 2018)
The environment (nature) is one of the most important aspects of life that needs to be considered when referring to and regarding sustainable development. This article aims to describe environmental management based on local knowledge using the case study conducted focusing on Mbatakapidu. The environment, which is a space for people to create a sustainable livelihood, is increasingly being disturbed by the acts of humanity itself. However, we cannot deny that in addition to these conditions, there are still local communities that always strive to create a balance between human and the environment. One of them is a local community in Mbatakapidu. This study used a qualitative approach with a case study perspective. The data collection was done by conducting in-depth interviews with the informants. The six informants were determined purposively. The results of this study show that people of Mbatakapidu trust that there are spirits who inhabit the springs and forests. This is a form of local wisdom that makes them tend to hold on to destructive action against the forest. The people of Mbatakapidu make nature their friend, and seek not to exploit but desire to maintain the sustainability of nature with the traditional local knowledge that they have. It implies that the Mbatakapidu people are obedient to Marapu. The values embraced by Marapu makes people harmonise their life with the natural environment. Therefore, the act of field (savannah) burning turned out to be mobilised by the individual and not at the instigation of local values as believed by the Mbatakapidu.